ИСЛЕДОВАНИЯ ЖАНА ВИВЬЕ АНГЛИЙСКОЙ ЛИТЕРАТУРЫ ПУТЕШЕСТВИЙ («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article is devoted to the monograph of the French literary scholar Jean Vivier, “English Travel Stories of the 18th Century.” The author of the monograph, studying English literature of the Enlightenment from different angles, reveals many new aspects of travel works, their connections and similarities with other genres of this era, and offers his own new interpretation of the topic.
Keywords: travel literature, diary, novel, narrative, image, author, traveler.